Sosialisasi Potensi Jalur Rempah di Barat Selatan Aceh - Inayatillah; Rahmawati, Putri; Ramli; Kurniawan, Ade; Hamsa, Amrizal; Wahyunita, Weni; Azizah (MEUSEURAYA - Jurnal Pengabdian Masyarakat, 2023)
The South West of Aceh has been the Spice route in Aceh, especially since the mid-16th century, when the Kingdom of Aceh began to plant pepper massively. The potential of pepper was then eroded by colonialism and conflict so that it was forgotten by the community. Socialization of the potential of the spice route is important in efforts to revitalize the potential of the spice route in South West Aceh. The purpose of the Socialization is to increase historical awareness, promote culture, strengthen the economy, encourage desire and innovation and trigger tourism. The socialization which was carried out on 18 and 19 May 2022 was aimed at community leaders, economic actors and the government in Southwest Aceh and South Aceh districts. The socialization received a positive response from both the community and the government. However, there needs to be cooperation as an effort by universities to encourage the revitalization of the potential of the spice route in South West Aceh..